Allergy to Red Meat: A Diagnosis Made by the Patient and Confirmed by an Assay for IgE Antibodies Specific for Alpha-1,3-Galactose - Mamadou Kaloga; Sarah Kourouma; Yao Isidore Kouassi; Elidje Joseph Ecra; Ildevert Patrice Gbery; Ange S. Allou; Almamy Diabate; Djokouehi Djeha; Abdoulaye Sangaré; Yao Pauline Yoboue (Karger Publishers, 2016)
We report the first case of allergy to red meat observed in Ivory Coast. A 49-year-old male presented with pruritus. The diagnosis of allergy to red meat was confirmed by an assay for IgE antibodies specific for alpha-1,3 galactose. Interestingly, the disease was considered a spell to the patient who was suspected of being a sorcerer by the community.